Canada. Significant Achievements 2019 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The main activities carried out by the Institute in Canada during 2019 are identified, with respect to the needs and interests of the country, strengthening issues such as health and food safety, project financing, economic and sustainable development, through the use of credits carbon; In addition, it collaborated in the development of forest and rural farms. Likewise, work was done on the inclusion of technology in agriculture, such as a digital platform, big data and artificial intelligence (AI), in order to promote innovative products and processes. Finally, work was done on the inclusion of young people in the agricultural sector, on the transfer of knowledge among international students, through internships and research.